PERANCANGAN MESIN STIRLING BETA TENAGA MATAHARI SEBAGAI PENGGERAK POMPA AIR - Alfa Ageng Santoso; Stenly Tangkuman; Michael E Rembet (JURNAL POROS TEKNIK MESIN UNSRAT, 2018)
Stirling engine is a heat engine that is driven by compression cycle and expansion of the working fluid in the form of gas. At different temperatures there will be a pressure difference which causes changes in heat energy to mechanical energy. Mechanical energy can be used to drive a water pump. This study aims to design a solar power Stirling beta engine to drive a water pump. There are six stages in this research. The first step is literature study. The second step is data collection. The third step is the calculation of the initial data. The fourth step is determining the initial dimensions. The fifth step is designing. The final step is a conclusion. Through this research, the Stirling Beta solar power has been successfully designed to drive the water pump. The design results can be described in five parts. The first part is the centralized temperature generated from a parabolic mirror with a diameter of 800 mm ranging from 937 K. The second part is the resulting cycle pressure of 1.79 bar. The third part is, at 3000 rpm, the Stirling engine producing a power of 496,6 Watt.. The fourth part is the torque produced by the engine of 30.07 Nm. In the last section, the dimensions of the Stirling engine design are 524 mm long, 167 mm wide and 200 mm high.Keywords: Stirling Beta, Solar Power, Water Pump